2016
DOI: 10.1159/000444023
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Test of the Differential Susceptibility Hypothesis Reveals a Genetic Predictor of Differential Response to Psychological Treatments for Child Anxiety Disorders

Abstract: Background: The differential susceptibly hypothesis suggests that certain genetic variants moderate the effects of both negative and positive environments on mental health and may therefore be important predictors of response to psychological treatments. Nevertheless, the identification of such variants has so far been limited to preselected candidate genes. In this study we extended the differential susceptibility hypothesis from a candidate gene to a genome-wide approach to test whether a polygenic score of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 46 publications
(62 reference statements)
3
121
0
1
Order By: Relevance
“…Although a significant association with lower MCS and MH scores was observed, the comparatively large standard error (SE) of the wGRS variable makes any conclusions on its relative importance challenging. The significant interaction term for wGRS-time predicting MH, indicating slower improvements in MH among individuals with high MDD genetic risk, is consistent with previous work indicating that depression genetic risk increases an individual's sensitivity to adverse environmental effects (38,39). Taken together, these findings support the notion that depression is a complex disorder with a modest, albeit important, genetic contribution comprising thousands of alleles of a small effect size.…”
Section: Discussionsupporting
confidence: 88%
“…Although a significant association with lower MCS and MH scores was observed, the comparatively large standard error (SE) of the wGRS variable makes any conclusions on its relative importance challenging. The significant interaction term for wGRS-time predicting MH, indicating slower improvements in MH among individuals with high MDD genetic risk, is consistent with previous work indicating that depression genetic risk increases an individual's sensitivity to adverse environmental effects (38,39). Taken together, these findings support the notion that depression is a complex disorder with a modest, albeit important, genetic contribution comprising thousands of alleles of a small effect size.…”
Section: Discussionsupporting
confidence: 88%
“…Genetic markers have been found in genes involved in the dopaminergic and serotonergic system. In particular, the carriers of the dopamine receptor D4 7-repeat alleles seem to be open to the environment, for better and for worse, as demonstrated in correlational as well as experimental studies and this genotype might be embedded in larger dopamine-related genetic pathways or polygenetic susceptibility scores (Belsky & van IJzendoorn, 2017;Keers et al, 2016;Lemery-Chalfant et al, 2018). Another marker of differential susceptibility is biological sensitivity to context, involving heightened stress and immune reactivity to negative stimuli in a chaotic and stressful environment, and at the same time elevated processing of positive stimuli in a structured, supportive environment (Boyce, 2019).…”
Section: Figurementioning
confidence: 99%
“…A recent study extended testing the DSH from a candidate gene approach to a GWAS approach36. A polygenic score of environmental sensitivity was derived in a sample of monozygotic twins by a novel method of assessing within-pair emotional problems as a function of genotype.…”
Section: Genetic Variation Influences Differential Sensitivity To Thementioning
confidence: 99%
“…There is also evidence that a small serotonergic PRS is associated with negatively biased attention following a negative mood induction57, while a PRS developed from a GWAS study in major depression disorder (MDD) has been shown to predict reduced cortical thickness in left medial frontal cortex; a region known to be disrupted in MDD58. A recent GWAS study has developed what we might call a PSS (polygenic sensitivity score) and found support for differential susceptibility in terms of heightened emotionality and response to psychological therapy in children with anxiety disorders36.…”
Section: Limitations Of Previous Research and The Way Forwardmentioning
confidence: 99%